Pattern Recognition Models: A Study and Review - Jahagirdar, Alifiya; Pawar, Dr. Vrushsen (IJRDO -Journal of Computer Science Engineering, 2016)
Pattern recognition has become more popular in the coming years and it’s applied in the wider areas ofresearch. The application areas spread into medicine, bioinformatics, data mining, speech recognition, handwritingrecognition, face recognition, objects in satellite images and many others. In this paper we have reviewed methodsused in pattern recognition. We will be studying different methods used for pattern recognition like statistical andstructural techniques, template matching, neural network, fuzzy method and hybrid models.